A new species of Zanthoxylum (Rutaceae) with a key to the species from Northeastern Brazil - Groppo, Milton; Pirani, José Rubens (Phytotaxa, 2017)
Zanthoxylum unifoliolatum Groppo & Pirani (Rutaceae), a new species from northeastern Brazil is here described and illustrated. To date, this species is known from a small number of collections from the state of Sergipe and considered endangered, given its restricted geographical distribution and the rapid deforestation of the Brazilian Atlantic Rainforest. Z. unifoliolatum can be readily distinguished from other Brazilian Zanthoxylum by its unifoliolate leaves, rather than pinnate leaves present in other Brazilian species of the genus A detailed description and illustrations of this new species are provided, as well as comments on the geographic distribution, phenology, generic relationships and conservation status. Additionally, a key to the species of Zanthoxylum from Northeastern Region of Brazil is provided.